Enzymatic Glycosylation of Ganoderma Terpenoid via Bacterial Glycosyltransferases and Glycoside Hydrolases - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang (Biomolecules)
Glycosylation is a critical enzymatic modification that involves the attachment of sugar moieties to target compounds, considerably influencing their physicochemical and biological characteristics. This review explored the role of two primary enzyme classes—glycosyltransferases (GTs) and glycoside hydrolases (GHs, glycosidases)—in catalyzing the glycosylation of natural products, with a specific focus on Ganoderma triterpenoids. While GTs typically use activated sugar donors, such as uridine diphosphate glucose, certain GHs can leverage more economical sugar sources, such as sucrose and starch, through transglycosylation. This paper also reviewed strategies for producing novel terpenoid glycosides, particularly recently isolated bacterial GTs and GHs capable of glycosylating terpenoids and flavonoids. It summarized the newly synthesized glycosides’ structures and biotransformation mechanisms, enhanced aqueous solubility, and potential applications. The regioselectivity and substrate specificity of GTs and GHs in catalyzing O-glycosylation (glucosylation) at distinct hydroxyl and carboxyl groups were compared. Furthermore, a special case in which the novel glycosylation reactions were mediated by GHs, including the formation of unique glycoside anomers, was included. The advantages and specific capabilities of GT/GH enzymes were evaluated for their potential in biotechnological applications and future research directions. Novel fungal triterpenoid glycosides produced through various glycosidases and sugars is expected to expand their potential applications in the future.